The Role of International Internship Student Program in Improving Student Learning Motivation at Somboonsart School, South Thailand - Moch Rifki Ramadhan; Imas Masruroh Imtihanah; Siti Romlah (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
This study aims to explain the role of International Internship Students (Indonesia-Thailand) at Somboonsart School in southern Thailand in order to increase students' learning motivation. This study uses a descriptive qualitative approach, namely describing and analyzing in depth and systematically a phenomenon by collecting data through interview and observation techniques. The results of the study show that the International Internship Student (Indonesia-Thailand) plays a very important role in increasing student learning motivation. The presence of International Internship Students creates a new atmosphere in the classroom, so that students become more active and enthusiastic in the teaching and learning process.